La Theanó di Michele Coniata fra παίγνιον erudito e rivelazioni ispirate - Carrozza, Marco (2023)
This paper aims to deepen, on the basis of studies personally conducted, further facets of a little-known late Byzantine epyllion (the Theanó by Michael Choniates), and yet extremely interesting both from a literary and a more broadly cultural point of view. In particular, we will focus on two sections of the poem, that is the proem and the inspired revelation of the (neo)pythagorean Theanó, announced from the very beginning of the poem. For the purpose of facilitating the consultation of the text and its first translation to a modern language, the lines examined are reproduced as annex to the following contribution.